Bad girl boogey [videorecording (DVD)] - Fanto, Lisa; Cassar, Prudence; Nguyen, Steven; McErlean, Iris (Darkstar Pictures, 2023)
Years after Angel's mother was brutally murdered in a killing spree by a psychopath wearing a mask believed to be cursed with hate, the killings have started again. Now, Angel must decide to either live in fear or find the killer before he, or it, slaughters everyone she holds dear.